JOURNAL WRITING AS AN ALTERNATIVE ASSESSMENT AND ITS WASHBACK ROLE TO THE STUDENT’S WRITING SKILL - Bedah; Oktaviana, Fadilla; Heryatun, Yayu (STKIP Citra Bakti, 2025)
This study examines journal writing as an alternative assessment method and its impact of washback on students' writing skills. With a qualitative approach, data was collected through literature studies, document analysis, and interviews with English teachers and grade X students at one of the high schools in Serang City, Banten. The results showed that journal writing improved students' vocabulary, grammar, ability to develop ideas, and fluency in writing. This activity also encourages reflective thinking, emotional engagement, and positive relationships between teachers and students. Teachers view journals as a useful formative tool, while students feel freer and less pressured than traditional assessments. Despite challenges such as time constraints, journal writing has a positive impact on students' cognitive, emotional, and metacognitive realms. The research concludes that journals support the continuous and relevant improvement of writing skills in 21st-century education